2023
DOI: 10.1186/s12864-023-09204-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and signatures of selection in BoHuai goat revealed by whole-genome sequencing

Abstract: Background Cross breeding is an important way to improve livestock performance. As an important livestock and poultry resource in Henan Province of China, Bohuai goat was formed by crossing Boer goat and Huai goat. After more than 20 years of breeding, BoHuai goats showed many advantages, such as fast growth, good reproductive performance, and high meat yield. In order to better develop and protect Bohuai goats, we sequenced the whole genomes of 30 BoHuai goats and 5 Huai goats to analyze the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…This study aimed to determine the population structure and genetic diversity to provide rational scientific conservation strategies for HX, MX, BM, and HZ pig populations. More and more studies have investigated the genetic diversity and population structure of various species of livestock (e.g., Min pig, Tongcheng pig, Tibetan sheep, Hainan cattle, and BoHuai goat) using whole-genome sequencing or SNP chips [14,[22][23][24][25][26][27]. For instance, Meng et al used a KPS porcine breeding chip v1 50K for SNP to study the genetic diversity of the Min pig-conserved population.…”
Section: Discussionmentioning
confidence: 99%
“…This study aimed to determine the population structure and genetic diversity to provide rational scientific conservation strategies for HX, MX, BM, and HZ pig populations. More and more studies have investigated the genetic diversity and population structure of various species of livestock (e.g., Min pig, Tongcheng pig, Tibetan sheep, Hainan cattle, and BoHuai goat) using whole-genome sequencing or SNP chips [14,[22][23][24][25][26][27]. For instance, Meng et al used a KPS porcine breeding chip v1 50K for SNP to study the genetic diversity of the Min pig-conserved population.…”
Section: Discussionmentioning
confidence: 99%
“…PDCD1LG2 (PDCD1 ligand 2) and SVIL are immunostimulatory genes. It has been reported that PDCD1LG2 in Bohuai goats and SVIL in Bos indicus are related to immunity [69,70]. PRDM16 is key in regulating the formation of brown fat cells and the production of brown fat [71][72][73].…”
Section: Functional Enrichment Analysismentioning
confidence: 99%
“…To date, several methodologies have been commonly employed for CNV detection, including comparative genome hybridization, extracting CNV data from SNP arrays, and whole-genome sequencing (WGS) approaches ( 24 26 ). Notably, recent research endeavors have delved into the investigation of the association between CNV in specific genes and a variety of phenotypic traits in animals, including growth characteristics in cattle ( 27 , 28 ), goats ( 29 31 ), sheep ( 32 ) and horses ( 33 38 ). These studies have also extended their focus to examine the link between CNVs and other vital phenotypes, such as reproduction traits ( 39 , 40 ) and disease resistance ( 7 , 41 ).…”
Section: Introductionmentioning
confidence: 99%